Teaching Speaking by Using Snake and Ladder Board Game - Soleman Dapa Taka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This research focuses on the use of the Snake and Ladder Board Game in teaching speaking to the tenth grade students at SMA Kristen Mercusuar Kupang. This research aims at finding out the appropriate way of teaching speaking by using snake and ladder board game for students in the tenth grade students at SMA Kristen Mercusuar Kupang..This research used Classroom Action Research (CAR). The subject of the research is the tenth grade students at SMA Kristen Mercusuar Kupang.. The procedure of the research applied two cycles namely cycle I and cycle II.  Every single cycle had fourth steps namely planning, implementing, observing and reflecting. The result of this research shown that there were significant developments on students speaking skill at the tenth grade students at SMA Kristen Mercusuar Kupang after conducting the treatments through snake and ladder board game. In which the score of a cycle 1 am 43,06 and the score of cycle II is 71,88. It means that the snake and ladder board game is an appropriate way to improve the students` speaking skills. In addition, the researcher found the result of the observation that almost all of the students gave positive responses, such as they gave attention seriously in learning process, they had been more active than before, make them happy and  enjoy the  class,  and  of  course  they could  improve  their  speaking toward snake and ladder board game in improving speaking skill